Acquiring academic literacy : a case of first-year extended degree programme students at Stellenbosch University - Van Schalkwyk, Susan C. (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Curriculum Studies))--Stellenbosch University, 2008.